THE RELATIONSHIP BETWEEN ANTI-THYROIDAL PEROXIDISE ANTIBODIES AND THYROID HORMONES (T3, T4 AND THYROID STIMULATING HORMONE TSH) AMONG PATIENTS WITH AUTOIMMUNE THYROID DISEASE - Al-Juburi, SalmanAziz; Taresh, Hashim Rahim; Mahmood, Abdulkareem A.; Majhul Al-Fatlawi, Rawaa Behlul (European Scientific Journal, ESJ, 2015)
Objectives: This Study was designed to investigate the role of the auto antibodies against thyroid peroxidise (TPO-Abs) and thyroid Hormones (T3, T4, TSH) in pathogenesis of Autoimmune Thyroid Disease (AITD). Methodology: Blood parameters of (90) individual who were attended to hormonal centre at AlSadder Medical City, in the period from January 2013 to June 2013 were measured, which includes Ttriiodothyronine (T3), Thyroxine or Tetraiodothyronine (T4), Thyroid Stimulating Hormone (TSH) and auto antibodies of thyroid peroxidise (TPO-Abs), the biostatic use difference between the maximum and minimum values (range). Results: the search results showed no significant increase in the rate of thyroid hormones (T3, T4, TSH) (p>0.2). Conclusion: The auto antibodies of thyroid peroxidise has no rule in function of thyroid hormones.